Preindustrial Control Simulations With HadGEM3‐GC3.1 for CMIP6. (13th December 2018) - Menary, Matthew B.; Kuhlbrodt, Till; Ridley, Jeff; Andrews, Martin B.; Dimdore‐Miles, Oscar B.; Deshayes, Julie; Eade, Rosie; Gray, Lesley; Ineson, Sarah; Mignot, Juliette; Roberts, Christopher D.; Robson, Jon; et al.
Abstract: Preindustrial control simulations with the third Hadley Centre Global Environmental Model, run in the Global Coupled configuration 3.1 of the Met Office Unified Model (HadGEM3‐GC3.1) are presented at two resolutions. These are N216ORCA025, which has a horizontal resolution of 60 km in the atmosphere and 0.25° in the ocean, and N96ORCA1, which has a horizontal resolution of 130 km in the atmosphere and 1° in the ocean. The aim of this study is to document the climate variability in these simulations, make comparisons against present‐day observations (albeit under different forcing), and discuss differences arising due to resolution. In terms of interannual variability in the leading modes of climate variability the two resolutions behave generally very similarly. Notable differences are in the westward extent of El Niño and the pattern of Atlantic multidecadal variability, in which N216ORCA025 compares more favorably to observations, and in the Antarctic Circumpolar Current, which is far too weak in N216ORCA025. In the North Atlantic region, N216ORCA025 has a stronger and deeper Atlantic Meridional Overturning Circulation, which compares well against observations, and reduced biases in temperature and salinity in the North Atlantic subpolar gyre. These simulations are being provided to the sixth Coupled Model Intercomparison Project (CMIP6) and provide a baseline against which further forced experiments may be assessed. Plain Language Summary: In this paper, we present the latest computer models of the joint atmosphere and ocean system. These models were developed at the U.K. Met Office Hadley Centre. They are designed to simulate the climate of the past, present, and future and to be used in scientific analysis and decision making. In this study, the are intended to simulate a continuous preindustrial state, to provide a reference level for future experiments and analysis. We present two resolutions of the same model, where the resolution is analogous to the number of pixels on, for example, a smartphone display. We find that the model with greater resolution also simulates many aspects of the global climate better than the model with lower resolution. These include El Niño, sea surface temperature variability in the Atlantic Ocean, and the depth of the AMOC in the North Atlantic. However, in other aspects, such as the strength of the major current circling Antarctica, this version is worse. Key Points: Preindustrial control simulations for CMIP6 with HadGEM3‐GC3.1 are presented using two model resolutions Our evaluation focuses on interannual variability in key climate indices The high‐resolution model shows improvements in ENSO, AMV, and in the depth structure of the AMOC. However, the ACC strength is worse